Kepemimpinan Kepala Madrasah dalam Lembaga Pendidikan Islam - Ahmad Noviansah; Mizaniya Mizaniya (ISLAMIKA, 2021)
This research is motivated by one of the key factors in supporting the success of madrasas with achievements is the leadership or management of madrasah principals. The quality of a madrasa leader is the key to the success of education in this educational institution. leadership style encompasses how a person acts in an organizational context Good leadership is always associated with school success. There is a significant correlation between school performance and the effectiveness of a leader. Edmonds mentioned that a good school is led by a good leader. Still in line, Rutherford stated that effective leaders always have a clear vision, so he also has a work program. Meanwhile, Rutter, as quoted by Sergiovanni, stated that the main is the key to the success and improvement of the quality of their students. However, to become a good leader is not only due to the prize factor, but also requires strong effort. A leader's cultural and social background and school become a very influential factor on the main leadership, it explains the social development of school residents and the leader's cultural and social background then becomes a necessity to express the success of an educational institution, such as Madrasas. This study aims to determine Islamic leadership in terms of theological perspective. The research method in this article is library research research using qualitative-interpretative data presentation. The research results of this journal are the Teacher as a leader in Islamic education with various terms that have moral, professional, and spiritual implications.